Dietary vitamin K supplementation and expression of proteins involved in skeleton development of senegalese sole (Solea senegalensis) - Richard, Nadège (2014)
In aquaculture, skeleton deformities are a serious problem as they affect growth, morphology, survival of fish and also increase productions costs and decrease market value of the final products. Since vitamin K is known for playing and important role in bone metabolism, the aim of this study was to investigate the effects of dietary vitamin K1 supplementation on skeleton deformities and on the expression of proteins involved involved in skeleton development of Senegalese sole.